Health literacy survey Portugal: A contribution for the knowledge on health and communications - Espanha, R. (2021)
The Portuguese Health Literacy Survey (HLS-PT) was developed and applied in Portugal on 2014, and its core goals were to contribute to an increase in the knowledge about the level of health literacy in Portugal and identify the main limitations, problems and obstacles associated with health literacy in Portuguese society, and to target the potential for future action in a way that will improve the current reality. In order to permit comparisons with other European countries, this study followed the methodology proposed by The European Health Literacy Survey HLS-EU (HLS-EU Consortium, 2012: Comparative Report on Health Literacy in Eight EU Member States). Our main conclusion shows that literacy level in Portugal is very similar to other countries of the European survey and that information sources are an important instrument to improve health literacy.